Effect of interest rate risk on financial performance the mediating role of banking security degree: evidence from the financial sector in Jordan - Al-Slehat, Zaher Abdel Fattah (Business: Theory and Practice, 2022)
The current study aims to determine the effect of interest rate risk on financial performance through the banking security degree as a mediating variable. The study population includes 13 Jordanian commercial banks from 2011 to 2018. To achieve the current study objectives, a descriptive and analytical approaches were used. Furthermore, Baron and Kenny’s test (1986) were adopted to examine the current study hypotheses. The results found that the banking security degree partially affects the relationship between interest rate risk and financial performance. Accordingly, this study provides a set of recommendations. Among them, we encourage policymakers and bank owners, and managers to develop efficient interest rate risk policies continuously in addition to strengthening the monetary and financial policies of the banking sector. They should strive to achieve a balance between each of the risks of interest rate, performance, and banking security degree.